(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Biocompatibility for the alloys which are used in the human body such as biomaterials depending on corrosion behavior. This study aim at research was to study the corrosion action and the biocompatibility of the samples of SS316L alloy uncoated and coated and compare the effect of coatings on corrosion behavior. Partially Stabilized Zirconia (PSZ) coating was do it by (EPD) technique on SS316L alloy . Structural investigation by using techniques including XRD , microstructure and crystalline of the coatings investigation in this study. Electrochemical measurement when effort the exams has been done in simulated body solution (Ringer and artificial saliva) in order to know the limitation and comparison the corrosion behavior of the gilder samples and clumsily samples as an evi- dence biocompatibility. Corrosion behavior for these coated specimens was more nobler than for the uncoated specimens.